2018
DOI: 10.1063/1.5040298
|View full text |Cite
|
Sign up to set email alerts
|

A soft-bent dimer composite exhibiting twist-bend nematic phase: Photo-driven effects and an optical memory device

Abstract: We report the influence of photoisomerization on a guest-host composite comprising a soft-bent dimer exhibiting the presently sought-after twist-bend nematic (NTB) phase, doped with small amounts of a calamitic photoactive azobenzene-based dimer that assumes a bent shape when photo-driven. Trans-cis photoisomerization of the latter compound leads to a substantial decrease in the nematic-isotropic and nematic-NTB transition temperatures. The results bring out the puzzling feature that the thermal stability of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…To date, a wide variety of bent LC dimers, oligomers, 64,[73][74][75][76][77] polymers, 78 and bent-core molecules 79,80 have been found to exhibit the N TB phase. In addition, N TB materials have been used for diverse applications such as photonic and optical devices, [81][82][83][84] gels, 85 elastic bodies, 86 and photoalignment technologies. 87 For characterization and application purposes, it is necessary to develop materials that exhibit the N TB phase over a wide temperature range, the room-temperature N TB phase, and its glass phase or N TB glass (N TB G).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide variety of bent LC dimers, oligomers, 64,[73][74][75][76][77] polymers, 78 and bent-core molecules 79,80 have been found to exhibit the N TB phase. In addition, N TB materials have been used for diverse applications such as photonic and optical devices, [81][82][83][84] gels, 85 elastic bodies, 86 and photoalignment technologies. 87 For characterization and application purposes, it is necessary to develop materials that exhibit the N TB phase over a wide temperature range, the room-temperature N TB phase, and its glass phase or N TB glass (N TB G).…”
Section: Introductionmentioning
confidence: 99%
“…18 Several techniques, including electro-optical measurements, 19 freeze-fracture transmission electron microscopy, 20,21 and resonant soft, hard, and tender X-ray scattering measurements, [22][23][24][25][26][27] suggest that the helical pitch of an N TB phase formed by several molecules is B10 nm, which is significantly shorter than the pitch of a typical chiral N phase or cholesteric phase exhibiting a helicoidal helix (generally hundreds of nanometers). Materials that exhibit the N TB phase have been employed for various LC applications, such as wavelength-tunable selective light reflection [28][29][30][31] and optical memory 32 devices, LC physical gels, 33 photo-switchable viscoelastic bodies, 34 and photoalignment technology. 35 To date, a number of bent LC dimers composed of two mesogenic structures connected with an odd-numbered oligomethylene spacer have been shown to exhibit the N TB phase.…”
Section: Introductionmentioning
confidence: 99%
“…In-depth reinvestigation of an LC dimer comprising two 4cyanobiphenyl arms connected by a heptamethylene spacer, 1ʺ,7ʺ-bis(4-cyanobiphenyl-4ʹ-yl)heptane (CB7CB) indicated that the Nx phase is the NTB phase [11] (here, it is to be noted that the Nx phase observed for the tetrapod molecule reported recently by Mandle et al was distinguished from the NTB phase [7]). Thus, identification of the NTB phase inspired extensive study on a large number of molecules that exhibit the NTB phase, such as bent LC dimers , various oligomers [35,[37][38][39][40][41][42][43][44][45][46], polymers [47], and bent-core molecules [48,49], and on related potential applications [50][51][52][53][54]. Electro-optical analysis [55], transmission electron microscopy [56,57], and soft, tender, and hard resonant X-ray scattering [34,[58][59][60][61] confirmed that the helical pitch of the NTB phase is considerably short, typically the length of several molecules or 10-20 nm.…”
Section: Introductionmentioning
confidence: 99%